Mechanism of choline deficiency and membrane alteration in postural orthostatic tachycardia syndrome primary skin fibroblasts. Issue 5 (2nd December 2014) - Schenkel, Laila C.; Singh, Ratnesh K.; Michel, Vera; Zeisel, Steven H.; da Costa, Kerry‐Ann; Johnson, Amy R.; Mudd, Harvey S.; Bakovic, Marica
ABSTRACT: Fibroblasts from a patient with postural orthostatic tachycardia syndrome (POTS), who presented with low plasma choline and betaine, were studied to determine the metabolic characteristics of the choline deficiency. Choline is required for the synthesis of the phospholipid phosphatidylcholine (PC) and for betaine, an important osmoregulator. Here, choline transport, lipid homeostasis, and mitochondria function were analyzed in skin fibroblasts from POTS and compared with control cells. The choline transporter‐like protein 1/solute carrier 44A1 (CTL1/SLC44A1) and mRNA expression were 2‐3 times lower in POTS fibroblasts, and choline uptake was reduced 60% ( P < 0.05). Disturbances of membrane homeostasis were observed by reduced ratios between PC:phosphatidylethanolamine and sphingomyelin:cholesterol, as well as by modified phospholipid fatty acid composition. Choline deficiency also impaired mitochondria function, which was observed by a reduction in oxygen consumption, mitochondrial potential, and glycolytic activity. When POTS cells were treated with choline, transporter was up‐regulated, and uptake of choline increased, offering an option for patient treatment. The characteristics of the POTS fibroblasts described here represent a first model of choline and CTL1/SLC44A1 deficiency, in which choline transport, membrane homeostasis, and mitochondrial function are impaired.—Schenkel, L. C., Singh, R. K., Michel, V., Zeisel, S. H., da Costa, K.‐A., Johnson, A. R., Mudd, H. S., Bakovic, M. Mechanism of choline deficiency and membrane alteration in postural orthostatic tachycardia syndrome primary skin fibroblasts. FASEB J. 29, 1663‐1675 (2015). www.fasebj.org